On Thin Flexible Wideband Printed Vivaldi Antenna for Sub-6 GHz Wearable Applications - Afroz, Sadia; Abdullah Al-Hadi, Azremi; Azemi, Saidatul Norlyana; Hoon, Wee Fwen; Padmanathan, Surentiran; Che Isa, Che Muhammad Nor; San Loh, Yen; Hao Tung, Lun; Ming Lim, Lai; Samsudin, Zambri; Mansor, Idris; Soh, Ping Jack (International Journal of Integrated Engineering, 2025)
The growing adoption of Body Area Networks (BANs) significantly enhanced the desire of wearable antennas. This study introduces a flexible wearable printed antenna based on an antipodal Vivaldi structure fabricated on a hybrid polyimide-polyester substrate utilizing screen printing fabrication technic, as well as a flexible dual-ring antenna utilizing copper tape and a polyester substrate. Compare to rigid antennas, flexible wearable antennas require meticulous fabrication and measurement processes due to their structural sensitivity. This paper provides a comprehensive analysis on the procedure of fabrication and considerations during measurement of the flexible wearable antennas, alongside a comparative analysis between them. These antennas exhibited satisfactory free-space performance, covering key 5G NR bands, including n48, n77, and n78. Printed antenna demonstrated wider resonance bandwidth oppose to the copper tape antenna and exhibited a higher degree of alignment among simulation and measurement. These findings indicate that the printed antenna offers superior performance and durability. To ensure its suitability for wearable applications, outcomes of the antenna was critically assessed placing on-body and under structural deformation. The measurement results validated the antenna's satisfactory performance, demonstrating a resonance bandwidth of 740 MHz when placed on the back, 710 MHz on the chest, and 650 MHz under a bending radius of 50 mm. Additionally, the measured results exhibited strong agreement with the simulation. Based on these assessments, the printed antenna is considered a feasible candidate for wearable applications.